Combined chemo-radiotherapy with organ preservation for invasive bladder cancer - Tester, William (Radiology and oncology (Ljubljana), 1997)
In North America, radial cystectomy remains the standard treatment for patients with muscle-invading bladder cancer. However, despite radical surgeryand resulting loss of normal urinary function, the expected 5 year survival is less than 50%. Radiation therapy has long been recognized a standard treatment option, capable of preserving organ function. However localcontrol with radiotherapy is only 30-50%. Incorporation of systemic chemotherapy into the primary management of invasive bladder cancer is an attractive strategy for several reasons. The risk of distant metasases is highand local treatment modalities cannot reduce that risk and preclinical studies have demonstrated synergistic cytotoxicity when cisplatin is combined with concurrent radiotherapy. Phase II clinical trials established chemo-radiotherapy with selective bladder preservation as an reasonable optionfor patients with muscle-invading bladder cancer. However, we still needto further improve local control rates, decrease the risk of non-invasive recurrences, decrease the risk of distant metastases and optimize quality of life of patients with muscle-invading bladder cancer.
Keywords: Bladder neoplasms; Combined modality therapy; Treatment outcome